Employee Productivity in Administrative Services (Case Study in Kedungcangkring Village, Jabon District, Sidoarjo Regency) - Firda Anggi Prianka; Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2021)
Low employee performance in providing administrative services is a problem in government agencies. The purpose of the study was to analyze and describe the performance of employees in the service of the Kedungcangkring village, Jabon sub-district, Sidoarjo district. The research method used in this study is a qualitative descriptive method using interviews, observation and documentation. The results showed that the productivity of the village apparatus was good. but needs to be improved again to work optimally.